2017
DOI: 10.1371/journal.pone.0186470
|View full text |Cite|
|
Sign up to set email alerts
|

De novo assembly and analysis of the transcriptome of Rumex patientia L. during cold stress

Abstract: BackgroundRumex patientia L. is consumed as a green vegetable in several parts of the world, and can withstand extremely low temperatures (-35°C). However, little or no available genomic data for this species has been reported to date. Here, we used Illumina Hiseq technology for transcriptome assembly in R. patientia under normal and cold conditions to evaluate how it responds to cold stress.ResultsAfter an in-depth RNA-Seq analysis, 115,589 unigenes were produced from the assembled transcripts. Based on simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…The number of DEGs in C3 and C4 were more than C1 and C2, and the number of down-regulated DEGs was less than the number of up-regulated DEGs in every library, particularly in C1 and C2. This is consistent with a result from previous reports in other plants under cold stress, such as rice ( Oryza longistaminata ) [ 39 ], patience dock [ 28 ], and crowtoe [ 25 ]. Furthermore, there were 433, 266, 791, and 1644 DEGs specifically modulated in C1, C2, C3, and C4, respectively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The number of DEGs in C3 and C4 were more than C1 and C2, and the number of down-regulated DEGs was less than the number of up-regulated DEGs in every library, particularly in C1 and C2. This is consistent with a result from previous reports in other plants under cold stress, such as rice ( Oryza longistaminata ) [ 39 ], patience dock [ 28 ], and crowtoe [ 25 ]. Furthermore, there were 433, 266, 791, and 1644 DEGs specifically modulated in C1, C2, C3, and C4, respectively.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, it is particularly useful for species that have not yet been sequenced. Based on RNA-Seq platforms, genome-scale transcriptome analyses were used to identify cold-stress-responsive genes in crowtoe ( Lotus japonicus ) [ 25 ], cassava ( Manihot esculenta ) [ 26 ], radish ( Raphanus sativus ) [ 27 ], patience dock ( Rumex patientia ) [ 28 ], peach [ 29 ], and Chinese yew ( Taxus chinensis ) [ 30 ]. Moreover, a recent study reported that two standard varieties of alfalfa (dormant and non-dormant) were sequenced using synthesis (SBS) technology, and several differentially expressed genes that were potentially related to fall dormancy were identified [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relative expression profiles of DEGs in the both resistant and susceptible evaluated using qRT-PCR were in complete agreement with the RNA-Seq data. This is in line with other studies, which showed almost the same level of fold changes between RNA-Seq data and qPCR [67,68].…”
Section: Validation Of Degs By Using Qrt-pcrsupporting
confidence: 93%
“…T. chinensis is a plant that is sensitive to cold, and this study was designed to investigate the changes in gene expression in T. chinensis seeds under cold stress. Due to the lack of genome sequences, we assembled the transcriptome for T. chinensis seeds using RNA-Seq, similar to the studies of other plants, such as Magnolia wufengensis [ 32 ], Passiflora edulis Sims [ 33 ], Hevea brasiliensis [ 20 ], and Rumex patientia [ 19 ]. We assembled 98,514 T. chinensis genes and 35,268 likely proteins expressed in the T. chinensis seeds in response to cold.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it facilitates analyses of gene expression in organisms whose genomes are not accessible. For example, using transcriptome sequencing and de novo assembly analysis, Liu et al investigated the transcriptome of Rumex patientia during cold stress and identified 66 genes that are putatively involved in the response to cold stress, including members of the MYB, AP2/ERF, CBF, Znf, bZIP, NAC, and COR families [ 19 ]. Mohamed Sathik et al employed transcriptome sequencing to study abiotic stress responsive genes in Hevea brasiliensis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%